De novo mutations in HNRNPU result in a neurodevelopmental syndrome. Issue 11 (25th September 2017) - Yates, T. Michael; Vasudevan, Pradeep C.; Chandler, Kate E.; Donnelly, Deirdre E; Stark, Zornitza; Sadedin, Simon; Willoughby, Josh; ,; ,; Balasubramanian, Meena
Abstract : Exome sequencing in the context of developmental disorders is a useful technique, but variants found need to be interpreted in the context of detailed phenotypic information. Whole gene deletions and loss‐of‐function‐mutations in the HNRNPU gene have been associated with intellectual disability and seizures in some patients. However, a unifying syndromic phenotype has not been previously elucidated. Here, we report a total of seven patients (six patients identified through the Wellcome Trust Deciphering Developmental Disorders study, with one additional patient), who have heterozygous de novo mutations in HNRNPU . These were found via trio‐based exome sequencing. All but one of the mutations is predicted to cause loss‐of‐function. These patients have dysmorphic features in common, including prominent eyebrows, long palpebral fissures, overhanging columella, and thin upper lip. All patients have developmental delay and intellectual disability (ID), ranging from moderate to severe. Seizures are common from early childhood. These initially occur in the context of febrile episodes. This series demonstrates common phenotypic features, including emerging dysmorphism, associated with heterozygous HNRNPU mutations. This allows us to define a novel neurodevelopmental syndrome, with a likely mechanism of haploinsufficiency.